Elevated KNSTRN as a potential indicator for triple-negative breast cancer progression and immune infiltration - Song, Yurong; Liu, Yuxi; Liu, Xiao; Qi, Minfang; Sun, Zhidong; Cao, Yuan (Frontiers in Immunology, 2025)
BackgroundKinetochore localized astrin/SPAG5 binding protein (KNSTRN) is a protein-coding gene pivotal for the mitotic spindle’s operation, ensuring accurate chromosome separation and transition into anaphase. Existing literature indicates that it is associated with a variety of cancers. However, there is a lack of research to confirm that it is related to the malignant phenotype and immune infiltration of triple-negative breast cancer (TNBC). The objective of this study was to ascertain the potential role of KNSTRN in TNBC prognosis, immune infiltration and progression.MethodsWe analyzed KNSTRN expression in TNBC using RNA-seq and single-cell transcriptome data from TCGA, GEO, and METABRIC datasets, correlating it with clinical features, prognosis, and immune infiltration. Functional enrichment analyses identified pathways regulated by KNSTRN in TNBC. In vitro siRNA knockdown in TNBC cell lines (MDA-MB-231 and BT549) assessed its impact on proliferation, migration, and DNA synthesis. RNA-seq was performed on BT549 cells with KNSTRN knockdown to validate the findings from the bioinformatic analysis. Immunohistochemistry was used to validate KNSTRN expression in tissue of patients with TNBC and other subtypes of breast cancer (Non-TNBC), as well as the association of KNSTRN expression and CD8+ T cell infiltration in TNBC.ResultsKNSTRN was significantly overexpressed in TNBC compared to those in other breast cancer subtypes and normal tissues. High expression of KNSTRN is associated with a poor prognosis in TNBC. Functional enrichment analysis revealed that KNSTRN-associated differentially expressed genes (DEGs) were involved in cell cycle regulation, metabolism, and immune response pathways. Immune infiltration analysis showed that high KNSTRN expression was associated with reduced infiltration of CD8+ T cells. In vitro experiments confirmed that KNSTRN knockdown inhibited TNBC cell proliferation and migration. RNA-seq on BT549 cells with KNSTRN knockdown also validated that KNSTRN played a role in promoting cell cycle progression and cell proliferation.ConclusionsKNSTRN is a candidate biomarker for TNBC prognosis and a potential target for immunotherapeutic strategies. Its overexpression in TNBC is associated with aggressive tumor behavior and an immunosuppressive microenvironment, highlighting its significance in TNBC pathogenesis and prognosis.